2017
DOI: 10.1111/mec.14417
|View full text |Cite
|
Sign up to set email alerts
|

Subfamily‐dependent alternative reproductive strategies in worker honeybees

Abstract: Functional worker sterility is the defining feature of insect societies. Yet, workers are sometimes found reproducing in their own or foreign colonies. The proximate mechanisms underlying these alternative reproductive phenotypes are keys to understanding how reproductive altruism and selfishness are balanced in eusocial insects. In this study, we show that in honeybee (Apis mellifera) colonies, the social environment of a worker, that is, the presence and relatedness of the queens in a worker's natal colony a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 89 publications
(172 reference statements)
3
15
1
Order By: Relevance
“…In contrast to the previously mentioned study (Yagound et al, ), we did not find more ovarioles and more activated ovaries in normal workers that drifted to foreign colonies compared to those that stayed in native colonies, but this result is easy to explain. Previous studies examined large numbers of normal workers and their tendency to migrate, while the total number of normal bees that drifted to other colonies was very low in our experiment (a maximum of 10 individuals in every colony), and this number was probably not sufficiently large to statistically determine the reproductive differences between bees in native and foreign nests, even if this tendency does exist in honeybee colonies.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to the previously mentioned study (Yagound et al, ), we did not find more ovarioles and more activated ovaries in normal workers that drifted to foreign colonies compared to those that stayed in native colonies, but this result is easy to explain. Previous studies examined large numbers of normal workers and their tendency to migrate, while the total number of normal bees that drifted to other colonies was very low in our experiment (a maximum of 10 individuals in every colony), and this number was probably not sufficiently large to statistically determine the reproductive differences between bees in native and foreign nests, even if this tendency does exist in honeybee colonies.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, some studies showed that ovary activation is related to the number of ovarioles (Makert, Paxton, & Hartfelder, ). Thus, the ovary activation in rebel workers collected from foreign colonies might have been higher because these individuals had more ovarioles in the ovary and spend life in alien colony, but we have no evidence to exclude the alternative scenario that rebel workers with more activated ovaries are more likely to drift to other colonies, as suggested by Yagound et al ().…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations